2009
DOI: 10.1080/14999010903014713
|View full text |Cite
|
Sign up to set email alerts
|

Violence Severity and Psychosis

Abstract: To examine whether severity of violence was associated with specific types of psychotic symptoms a retrospective file review of men found of unsound mind by the Queensland Mental Health Tribunal was conducted. The association between symptoms and three levels of violence were examined. Capgras delusions and command hallucinations were associated with homicide; acute danger; and threat/control-override symptoms with serious violence, and grandiose delusions with assault occasioning bodily harm. When previous vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…Keene and Holloway found no difference in psychotic symptoms across levels of violence (2000). Other studies reported a greater incidence of psychotic symptoms (paranoid ideation, command hallucinations, threat/control-override symptoms, Capgras symptoms) in more violent offenders compared to less violent offenders (Chan & Shehtman, 2019; Green et al, 2009). In one meta-analytic study injury severity did not moderate the relationship between violence and psychosis; rather, psychotic symptoms were associated with increased risk for violence at both mild and severe levels.…”
Section: Introductionmentioning
confidence: 93%
“…Keene and Holloway found no difference in psychotic symptoms across levels of violence (2000). Other studies reported a greater incidence of psychotic symptoms (paranoid ideation, command hallucinations, threat/control-override symptoms, Capgras symptoms) in more violent offenders compared to less violent offenders (Chan & Shehtman, 2019; Green et al, 2009). In one meta-analytic study injury severity did not moderate the relationship between violence and psychosis; rather, psychotic symptoms were associated with increased risk for violence at both mild and severe levels.…”
Section: Introductionmentioning
confidence: 93%
“…On the one hand, studies have been conducted that find a direct association of mental health issues (namely psychotic symptoms, paranoid ideation, mania, bipolar disorder, and PTSD) with aggressive and criminal behavior (Fazel et al, 2010; B. Green et al, 2009; R. Howard et al, 2017; Kelley, Thornton et al, 2020; Stueve & Link, 1997). On the other hand, researchers suggest that mental illnesses do not directly increase crime, but rather that this association is mediated by other variables.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research reporting associations between mental health issues and crime is, however, inconsistent and contradictory. On the one hand, studies have been conducted that find a direct association of mental health issues (namely psychotic symptoms, paranoid ideation, mania, bipolar disorder, and PTSD) with aggressive and criminal behavior (Fazel et al, 2010;B. Green et al, 2009;R.…”
Section: Psychological Predictors Of Crimementioning
confidence: 99%
“…Komorbidität mit Substanzmissbrauch [3,19,[20][21][22][23] Komorbidität mit antisozialer Persönlichkeitsstörung [20,23,24,25] Eltern, bei denen Substanzmissbrauch und/oder Delinquenz bekannt ist [21] systematisierter Wahn mit hoher Wahndynamik, welcher die inneren Normen und Kontrollen ausschaltet; vor allem Verfolgungswahn, Eifersuchtswahn, Überzeugung, kontrolliert zu werden, Ichstörungen; [26,27,28,29] Threat/Control-override [20,29,30,31,32], d. h. der Patient ist der Überzeugung, dass sein Verstand von Kräften, die außerhalb seiner Kontrolle liegen, dominiert wird, ihm fremde Gedanken aufgezwungen werden, andere Menschen ihm Schaden zufügen wollen frühere Viktimisierung [20,33] junges Alter [3] gewalttätige Vortaten [22,30,34] neuropsychologische Defizite niedriger sozioökonomischer Status Risikoeinschätzung und primäre Prävention sind nicht auf den stationären Bereich beschränkt. Auch in der psychiatrischen Praxis ist primäre Prävention von großer Bedeutung.…”
Section: Risikofaktoren Für Gewaltdelinquenz Bei Schizophrenenunclassified